Impact analysis of Covid on supply chain performance - بن رميلة, عبد الرحيم; إفوراح , حسين; حداد, زهير (khazzartech الاقتصاد الصناعي, 2023)
This paper focuses on illustrating the reasons and problems that supply chain managers confront in order to adapt and cope with this health catastrophe on a continual basis. Our contribution consists of analyzing the impact of Covid 19 on supply chain performance as well as identifying the best tactics and solutions in terms of methodologies and tools used by supply chain specialists in times of crisis. Our technique entails first developing interviews based on a theoretical study and documentary and bibliographical research on the supply chain, and then sharing these interviews online with the aid of supply chain specialists and through the professional network Linkedln. The findings demonstrate that the Covid problem has a significant influence on the supply chain: first, downstream, with supply delays and uncertainty, and then demand; secondly, upstream, with distribution issues, outages, and overstock for specific goods.